2006
DOI: 10.1002/bsl.740
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of patients rehabilitated through a New Zealand forensic psychiatry service: a 7.5 year retrospective study

Abstract: This paper describes a 7.5 year retrospective study of all patients discharged from inpatient forensic services to forensic community team (FCT) follow-up from the Auckland Regional Forensic Psychiatry Service. Patients' files were studied for clinical, criminal, and risk data, type of service delivered, and final level of function achieved in the community. Rearrest, re-hospitalization, and reimprisonment data were obtained from clinical, court, and prison records.105 patients were included. The most common d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 22 publications
5
39
3
Order By: Relevance
“…627–640) demonstrate the overall effectiveness of maintaining individuals on CR in community‐based programming. Findings from these articles are consistent with recent research on CR, demonstrating modest recidivism rates and a low rearrest rate, especially for violent offenses (see also Callahan & Silver, ; Simpson, Jones, Evans, & McKenna, ; Vitacco et al ., ; Vitacco, Vauter, Erickson, & Ragatz, ). Further evidence underscoring the generally positive results surrounding CR should be welcomed by policymakers who have a stake in mental health programming.…”
Section: Placement and Success On Crsupporting
confidence: 86%
“…627–640) demonstrate the overall effectiveness of maintaining individuals on CR in community‐based programming. Findings from these articles are consistent with recent research on CR, demonstrating modest recidivism rates and a low rearrest rate, especially for violent offenses (see also Callahan & Silver, ; Simpson, Jones, Evans, & McKenna, ; Vitacco et al ., ; Vitacco, Vauter, Erickson, & Ragatz, ). Further evidence underscoring the generally positive results surrounding CR should be welcomed by policymakers who have a stake in mental health programming.…”
Section: Placement and Success On Crsupporting
confidence: 86%
“…The topic of community‐based forensic treatment for mentally ill offenders has also been of great international interest (see Table ). The studies by Ong et al () and Simpson et al () demonstrate rates of recidivism comparable to or even less than the more recent American studies. Skipworth et al () found significantly higher rates of recidivism, but this may be related to the longer duration of follow‐up (which is often linked to higher recidivism rates) and the study follow‐up beginning in 1976, prior to the advent of more intensive community supervision.…”
Section: Ngri Rehospitalization and Recidivism Literaturementioning
confidence: 75%
“…In a follow-up of all forensic patients discharged from the Auckland Regional Forensic Psychiatry Service in New Zealand from 1998 to 2004, the majority were single men with a mean age of 38 years. Eighty-nine percent had a primary psychotic diagnosis (predominantly schizophrenia and schizoaffective disorder), 22% were diagnosed with a personality disorder, 78% had a co-morbid substance abuse disorder, and most had a criminal history where violence was the predominant index behavior (Simpson, Jones, Evans, & McKenna, 2006). An evaluation of data from the Department of Health and Ministry of Justice in England and Wales found that 88% of the forensic services population was male, 84% were between 26 and 64 years of age, and nearly half were detained for violent or sexual offenses (Rutherford & Duggan, 2007).…”
Section: Forensic Populationsmentioning
confidence: 98%